"Dual‐Template" Synthesis of One‐Dimensional Conductive Nanoparticle Superstructures from Coordination Metal–Peptide Polymer Crystals. Issue 24 (5th July 2013) - Rubio‐Martínez, Marta; Puigmartí‐Luis, Josep; Imaz, Inhar; Dittrich, Petra S.; Maspoch, Daniel
Abstract Bottom‐up fabrication of self‐assembled structures made of nanoparticles may lead to new materials, arrays and devices with great promise for myriad applications. Here a new class of metal–peptide scaffolds is reported: coordination polymer Ag(I)‐DLL belt‐like crystals, which enable the dual‐template synthesis of more sophisticated nanoparticle superstructures. In these biorelated scaffolds, the self‐assembly and recognition capacities of peptides and the selective reduction of Ag(I) ions to Ag are simultaneously exploited to control the growth and assembly of inorganic nanoparticles: first on their surfaces, and then inside the structures themselves. The templated internal Ag nanoparticles are well confined and closely packed, conditions that favour electrical conductivity in the superstructures. It is anticipated that these Ag(I)‐DLL belts could be applied to create long (>100 μm) conductive Ag@Ag nanoparticle superstructures and polymetallic, multifunctional Fe3O4@Ag nanoparticle composites that marry the magnetic and conductive properties of the two nanoparticle types.